Digest of Action Taken by Bombay Government on the Summary of the Recommendations of the Planning Commission on the Five Year Plan - Planning Commission (Planning Commission, 1956)
The First Five Year Plan, Summary of Reformation in the First Five Year Plan Assessment of Resources Public Administration and Public Cooperation Reorganisation of District Organisation Public Cooperation in National Development.
Government of Bombay